2017
DOI: 10.3892/ol.2017.5687
|View full text |Cite
|
Sign up to set email alerts
|

Decreased calpain 6 expression is associated with tumorigenesis and poor prognosis in HNSCC

Abstract: Calpains are a family of intracellular cysteine proteases involved in various biological processes. Previously, the family was identified to have abnormal expression in several types of malignant tumor. Calpain 6 was less well known; however, it was recently identified to be involved in the carcinogenesis of certain types of malignant tumor. However, the expression of calpain 6 in head and neck squamous cell carcinoma (HNSCC) remains unclear. A total of six datasets from the Gene Expression Omnibus (GEO) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…Xiang et al examined CAPN6 expression in HNSCC, including tongue cancer, laryngeal cancer and nasal cancer ( 42 ). The results of their study demonstrated that the expression of CAPN6 in HNSCC tissues was significantly decreased, which was in complete contrast to the observations of other tumor studies, as mentioned above.…”
Section: Capn6 In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiang et al examined CAPN6 expression in HNSCC, including tongue cancer, laryngeal cancer and nasal cancer ( 42 ). The results of their study demonstrated that the expression of CAPN6 in HNSCC tissues was significantly decreased, which was in complete contrast to the observations of other tumor studies, as mentioned above.…”
Section: Capn6 In Tumorsmentioning
confidence: 99%
“…CAPN6 expression also varies between different tumor stages of HNSCC, and it differs significantly between different T stages, although there is no significant difference between different N stages and different tumor grades. In addition, the expression of CAPN6 and the survival rate of patients with HNSCC exhibit a positive association ( 42 ). However, it is not clear whether the expression of CAPN6 is directly linked to the occurrence of HNSCC, or whether HNSCC tumor growth or metastasis leads to CAPN6 downregulation.…”
Section: Capn6 In Tumorsmentioning
confidence: 99%
“…Вероятно, при увеличении выборки больных РГ могут быть получены значимо ассоциированные результаты. Возможно, уровень экспрессии и значимые корреляции кальпаинов 1 и 2 с клинико-морфологическими характеристиками зависят от других характеристик опухоли [10] или связаны с важной ролью других членов семейства кальпаинов в патогенезе РГ [11,12].…”
Section: результаты и обсуждениеunclassified
“…высоким уровнем экспрессии EZR, что косвенно может указывать на активацию процессов инвазии [9,10]. В целом, результаты подтверждаются данными о тканеспецифичности кальпаинов, например о связи рака гортани с CAPN10 [11], а уровень экспрессии CAPN6 отрицательно коррелирует с исходом заболевания у больных плоскоклеточным раком головы и шеи [12]. Тем не менее результаты нашего исследования говорят о необходимости детального изучения возможных молекулярных механизмов взаимодействия кальпаиновой системы и белков, ассоциированных с ремоделированием цитоскелета, на транскриптомном и протеомном уровне.…”
Section: результаты и обсуждениеunclassified
“…The expression of neutrophil gelatinase-associated lipocalin was lower in HNSCC than in normal tissues, and was correlated with the tumorigenesis of HNSCC (6). Calpain 6 expression was significantly decreased in HNSCC and positively associated with the survival rate of patients with the disease, thereby indicating the role of calpain 6 as a tumor suppressor in HNSCC (7). However, due to the limited sample sizes, previous studies may provide false predictions.…”
Section: Introductionmentioning
confidence: 99%